Kansvatter: Die rustelose lewe van Ben Viljoen - Coetzee, Emile (Scientia Militaria - South African Journal of Military Studies, 2021)
To write a biography is a daunting task but if done correctly and fairly, it can be amagnificent piece of historical literature. A biography, and especially an autobiography,is a literary genre that can assist any historian to see past events directly through the eyesof the person about whose life is being written. Some historical figures can boast a longlist of biographies due to their popularity during their lifetime or shortly after it. Othersare either merely mentioned briefly in other publications or their biographies are limiteddue to a variety of external factors. When it comes to Benjamin Johannis (or is it BarendJohannes?) Viljoen, his life story is finally explained thoroughly for the first time by theStellenbosch historian, Dr Carel van der Merwe.